Charting the future of Brazil’s electricity: a multicriteria analysis of northeastern power strategies amidst climate challenge - Clécio Barbosa Souza Júnior; Johann Köppel; Maria do Carmo Sobral (Revista Brasileira de Ciências Ambientais)
The article addresses the challenges faced by regions under water stress, such as conflicts over water use, environmental degradation, and water resource scarcity, intensified by climate change. In areas dependent on hydropower generation, these problems are exacerbated, highlighting the need to transition to more sustainable and resilient energy sources. The study emphasizes the importance of multifaceted criteria for an effective transition of the electricity matrix in semi-arid regions, taking into account economic, technical, environmental, and social aspects. Focusing on the São Francisco River basin in Northeastern Brazil, where the energy matrix is predominantly hydroelectric, the study uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) to evaluate alternative scenarios, analyzing options for wind, solar, and thermoelectric energy. The methodology adopted included the close collaboration of experts in defining and weighting essential criteria, covering economic, technical, environmental, and social aspects. The results show that, within the same group, options that involve greater reductions in hydroelectric generation are more advantageous. Analyzing the ranking among all alternatives, the group that includes higher expansion of wind energy presents the most viable options, followed by the reference strategy (based on average annual generation) and the group with greater expansion of solar capacity. Increasing the share of gas-fired thermoelectric power is considered a less favorable solution according to the criteria used in the model.